Project-Based Learning as a Creative and Innovative Method in EFL: Challenges and Teachers’ Strategies - I GAP Novita Sari Paragae (English Teaching and Linguistics Journal (ETLiJ), 2026)
Project-based learning (PjBL) has been known as an effective, creative, and innovative teaching method in the EFL context. Some previous research has highlighted the effectiveness of PjBL and the challenges faced by teachers in its implementation. However, the research that explicitly explores the strategies implemented by teachers to overcome the challenges is rare, especially in the context of Senior High School. To fill the gap, this study aims to explore teachers’ perception on the challenges faced in PjBL implementation and the strategies employed to overcome the challenges. This study was conducted in a descriptive qualitiative design and collected the data through interviews, classroom observation, and document analysis among English teachers who have experience in implementing PjBL. The data were analyzed by using thematic analysis to identify the main themes appears from teachers’ practice and experience. The study found that the implementation of PjBL faces some challenges, such as (1) time limitation and curriculum demands, (2) a variety of students’ readiness and ability, (3) teachers' workload, and (4) difficulties in doing project-based assessment. In addition, the teachers employed adaptive strategies to overcome the challenges: (1) flexible time management and project simplification, (2) scaffolding and differentiated learning, (3) collaboration with fellow teachers, and (4) assessment and rubric adaptation. By highlighting teachers’ strategy explicitly, this study gives contribution to PjBL literature by providing practical insights into a more sustainable implementation of PjBL in the EFL context.